Validation of international recommendations on bone marrow aspiration for Pediatric Immune Mediated Thrombocytopenic Purpura - Bilal, Hina (International Journal of Pathology, 2020)
Introduction: Immune medicated thrombocytopenic purpura (ITP) is diagnosed on clinical basis with normal peripheral smear findings. Bone marrow examination is done to rule out leukemia or aplastic anemia. In most of cases with typical history and peripheral smear findings diagnosis is not changed after a bone marrow examination.Objective: Objectives of this study were to study clinico-hematological findings in cases of immune medicated thrombocytopenic purpura and to validate findings of our study with international recommendations.Methods: This study included fifty pediatric patients who presented with suspicion of ITP or with thrombocytopenia and turned out to be ITP. Their clinico-pathological signs and symptoms and peripheral blood smears and bone marrow findings were noted.Results: Age range of patients in this study was from five months to twelve years. Female to male ratio was 54%: 46% respectively. All patients presented with history of cutaneous bleeding. None of patients had lymphadenopathy. Splenomegaly was present in 4% of cases. 50% of patients had platelet count of less than 20,000 x109/L and 16% had platelet count between 50,000 x109/L -100,000 x109/L. Bone marrow examination in all patients showed normal myeloid, erythroid and lymphoid series cells with prominent megakaryocytes. 94 % of patients showed increased number of megakaryocytes and 78% of patients showed immature forms of megakaryocytes on bone marrow aspiration.Conclusion: Bone marrow examination is not required as a first line investigation for diagnosis in a typical clinical scenario. The routine of using bone marrow examination as a first line diagnostic tool in childhood ITP should be avoided unless clinically indicated